Improving Listening Skills in Seventh Grade Students Through English Songs - Rajabasa Rajagukguk, Johan; Pascal Lumumba (Edelweiss : Journal Of Innovation In Educational Research, 2024)
The aim of this journal is to explore the role of music in enhancing listening skills, which is one of the core competencies in English language learning, alongside speaking, reading, and writing. These essential skills are categorized into productive (speaking and writing) and receptive (listening and reading) abilities. Music and songs play a critical role in both educational and developmental contexts. Incorporating music into classroom settings offers numerous advantages. While there are differing opinions on the use of songs for teaching foreign languages, employing music during listening exercises is widely recognized as an effective strategy for improving listening skills. English songs, in particular, can be quite captivating, fostering student engagement and improving performance in listening activities. However, there are limitations to using music for this purpose, such as the potential inaccuracy of lyrics in popular songs and the challenge of poor sound systems in classrooms, which can hinder the effectiveness of music-based listening exercises